THE FOUNDATIONS OF SPEECH ACT THEORY: AUSTIN'S APPROACH IN MODERN PRAGMATICS - Kushakova Nodira Odilovna,Yusufova Feruza (International Journal of Literature and Language Studies, 2026)
This article examines Speech Act Theory as one of the fundamental approaches in modern linguistic pragmatics. The study analyzes the theoretical foundations established by John L. Austin and the subsequent development of the theory in the works of John R. Searle. Particular attention is paid to the concept of speech acts as intentional communicative actions performed according to social conventions. The paper discusses the three components of speech acts—locutionary, illocutionary, and perlocutionary acts—as well as the notion of performative utterances and felicity conditions. Furthermore, the article examines Searle’s classification of illocutionary acts, including representatives, directives, commissives, declaratives, and expressives, together with the distinction between direct and indirect speech acts. The role of speech acts in pragmatic meaning, interpersonal communication, intercultural interaction, and translation studies is also considered. The findings demonstrate that Speech Act Theory provides an effective framework for explaining how linguistic expressions function as social actions and how communicative intentions are realized in various discourse contexts.